2021
DOI: 10.1111/all.15194
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for systemic reactions in typical cold urticaria: Results from the COLD‐CE study

Abstract: Background Cold urticaria (ColdU), that is, the occurrence of wheals or angioedema in response to cold exposure, is classified into typical and atypical forms. The diagnosis of typical ColdU relies on whealing in response to local cold stimulation testing (CST). It can also manifest with cold‐induced anaphylaxis (ColdA). We aimed to determine risk factors for ColdA in typical ColdU. Methods An international, cross‐sectional study COLD‐CE was carried out at 32 urticaria centers of reference and excellence (UCAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
1
25
0
2
Order By: Relevance
“…1 Cold-induced anaphylaxis (ColdA), which may result in fatality, 2 is common in typical cold urticaria (ColdU), and risk factors for ColdA have recently been identified for the first time. 3 As of now, it is largely unclear how often patients with ColdU (i) receive adrenaline treatment and (ii) are provided with an AAI. 2 A study by Gernez et al in the USA showed that 48% of allergy and immunology specialists prescribe an AAI to ColdU patients less than 10% of the time.…”
Section: Adrenaline Autoinjector Is Underprescribed In Typical Cold U...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Cold-induced anaphylaxis (ColdA), which may result in fatality, 2 is common in typical cold urticaria (ColdU), and risk factors for ColdA have recently been identified for the first time. 3 As of now, it is largely unclear how often patients with ColdU (i) receive adrenaline treatment and (ii) are provided with an AAI. 2 A study by Gernez et al in the USA showed that 48% of allergy and immunology specialists prescribe an AAI to ColdU patients less than 10% of the time.…”
Section: Adrenaline Autoinjector Is Underprescribed In Typical Cold U...mentioning
confidence: 99%
“…Less than 10% of patients with ColdA received adrenaline and less than 40% of them have an AAI. ColdU patients need to be screened by specialists and non-specialists to identify those with ColdA risk factors (Table 2), 3 which may also include underlying clonal mast cell disorder. 6 Prescribing an AAI to patients at risk of ColdA needs to be com- Note: Data are given as no.…”
Section: Adrenaline Autoinjector Is Underprescribed In Typical Cold U...mentioning
confidence: 99%
“…3,8,9 About 40% of ColdU patients develop systemic reactions, such as vertigo, nausea, hypotension, dyspnea, or anaphylaxis, in addition to wheals or angioedema. 8,10 Many ColdU patients experience a severe impairment in their quality of life, as they frequently avoid outdoor activities or contact with cold water, such as swimming 11 but can also experience symptoms in daily activities such as preparation of cold food, wet cleaning, and skin contact with cool objects, for example, toilet seats.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The spectrum of reactions to these triggers varies widely, ranging from mild localized whealing to dangerous generalized and systemic reactions and potentially life‐threatening angioedema 3,8,9 . About 40% of ColdU patients develop systemic reactions, such as vertigo, nausea, hypotension, dyspnea, or anaphylaxis, in addition to wheals or angioedema 8,10 11 but can also experience symptoms in daily activities such as preparation of cold food, wet cleaning, and skin contact with cool objects, for example, toilet seats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation